General Education Teachers’ Perspectives on Challenges to the Inclusion of Students with Intellectual Disabilities in Qatar - Sughra Darwish; Ali Alodat; Maha Al-Hendawi; Annalisa Ianniello (Education Sciences, 2025)
This study examines the challenges that general education teachers face in implementing inclusive education for students with intellectual disabilities in Qatar. Employing a mixed-methods approach, quantitative data were collected from 255 teachers via a structured questionnaire, complemented by qualitative insights from semi-structured interviews with five participants. The findings indicate that teachers encounter moderate to high levels of difficulty, particularly in areas related to the school environment and the availability of educational resources. Significant demographic differences were observed, with male teachers and those working in primary schools reporting greater perceived barriers. Thematic analysis revealed six key factors influencing teachers’ perceptions: student diversity, instructional practices, teacher preparedness, school culture and environment, family and community involvement, and logistical challenges. Despite national policy support for inclusive education, the study reveals ongoing deficits in teacher training, institutional backing, and resource provision. These findings underscore the complex intersection of individual, institutional, and societal factors shaping inclusive education efforts. The study offers valuable insights for localizing inclusive education efforts in Qatar and similar contexts, with implications for educators, policymakers, and educational leaders committed to fostering equitable learning environments.